Notes of a crocodile - Qiu, Miaojin 1969-1995 (New York Review Books, 2017)
"Set in the post-martial-law era of 1990s Taipei, Notes of a Crocodile depicts the coming-of-age of a group of queer misfits discovering love, friendship, and artistic affinity while hardly studying at Taiwan's most prestigious university. Told through the eyes of an anonymous lesbian narrator nicknamed Lazi, Qiu Miaojin's cult classic novel is a postmodern pastiche of diaries, vignettes, mash notes, aphorisms, exegesis, and satire by an incisive prose stylist and countercultural icon. Afflicted by her fatalistic attraction to Shui Ling, an older woman who is alternately hot and cold toward her, Lazi turns for support to a circle of friends that includes the devil-may-care, rich-kid-turned-criminal Meng Sheng and his troubled, self-destructive gay lover Chu Kuang, as well as the bored, mischievous overachiever Tun Tun and her alluring slacker artist girlfriend Zhi Rou. Bursting with the optimism of newfound liberation and romantic idealism despite corroding innocence, Notes of a Crocodile is a poignant and intimate masterpiece of social defiance by a singular voice in contemporary Chinese literature"...
Keywords: FICTION / Lesbian; FICTION / Coming of Age; Lesbians -- Fiction; Women -- Taiwan -- Fiction; Gays -- Taiwan -- Fiction; Taipei (Taiwan) -- History -- 20th century -- Fiction; Bildungsromans